2023
DOI: 10.20944/preprints202312.0698.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demyelination in Patients with Post-COVID Depression

Marina Khodanovich,
Mikhail Svetlik,
Daria Kamaeva
et al.

Abstract: Depression is one of the most severe sequelae of COVID-19, with major depressive disorder often characterized by disruption in white matter (WM) connectivity , stemming from changes in brain myelination. This study aimed to quantitatively assess brain myelination in clinically diagnosed post-COVID depression using recently proposed MRI method, macromolecular proton fraction (MPF) mapping. The study involved 63 recovered COVID-19 patients (52 mild, 11 moderate, 2 severe) at 13.5±10.0 months post-recovery, with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 91 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…The study showed more extensive brain demyelination in patients with post-COVID depression in comparison to controls and post-COVID patients without clinically diagnosed depression. Moreover, our study identified demyelination of inferior frontooccipital fasciculus (IFOF) as the primary predictor of PCD presence and severity [68]. Anatomically, the IFOF connects early visual processing in the occipital lobe (cuneus and lingual gyri) and the parietal regions with frontal lobe regions [76,77] and also includes the connections between the cingulo-opercular and frontoparietal networks [77,78].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The study showed more extensive brain demyelination in patients with post-COVID depression in comparison to controls and post-COVID patients without clinically diagnosed depression. Moreover, our study identified demyelination of inferior frontooccipital fasciculus (IFOF) as the primary predictor of PCD presence and severity [68]. Anatomically, the IFOF connects early visual processing in the occipital lobe (cuneus and lingual gyri) and the parietal regions with frontal lobe regions [76,77] and also includes the connections between the cingulo-opercular and frontoparietal networks [77,78].…”
Section: Discussionmentioning
confidence: 83%
“…Since microglial and astroglial reactivation lead to impaired oligodendrocyte functioning and renewal [65][66][67], demyelination or decreased remyelination also might play an important role in cognitive changes in PCD patients. The MRI study performed in the same group of PCD patients supported the hypothesis of brain demyelination after COVID-19 [68]. In that study, we used quantitative macromolecular proton fraction (MPF) mapping [69][70][71] that strongly correlated with myelin content [69,[72][73][74][75].…”
Section: Discussionmentioning
confidence: 84%
“…The study showed more extensive brain demyelination in patients with post-COVID depression in comparison to controls and post-COVID patients without clinically diagnosed depression. Moreover, our study identified the demyelination of the inferior fronto-occipital fasciculus (IFOF) as the primary predictor of PCD presence and severity [ 94 ]. Anatomically, the IFOF connects early visual processing in the occipital lobe (cuneus and lingual gyri) and the parietal regions with frontal lobe regions [ 102 , 103 ], and also includes the connections between the cingulo-opercular and frontoparietal networks [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since microglial and astroglial reactivation lead to impaired oligodendrocyte functioning and renewal [91][92][93], demyelination or decreased remyelination might also play important roles in cognitive changes in PCD patients. An MRI study performed on the same group of PCD patients supported the hypothesis of brain demyelination after COVID-19 [94]. In that study, we used quantitative macromolecular proton fraction (MPF) mapping [95][96][97] that strongly correlated with myelin content [95,[98][99][100][101].…”
Section: Possible Physiological Basis Of Covid-19-related Cognitive C...mentioning
confidence: 96%